2005
DOI: 10.1021/nl0515910
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Effect in Cu Nanowires

Abstract: A rubber-like pseudoelastic behavior is discovered in single-crystalline face-centered-cubic (FCC) Cu nanowires in atomistic simulations. Nonexistent in bulk Cu, this phenomenon is associated primarily with a reversible crystallographic lattice reorientation driven by the high surface-stress-induced internal stresses due to high surface-to-volume ratios at the nanoscale level. The temperature-dependence of this behavior leads to a shape memory effect (SME). Under tensile loading and unloading, the nanowires ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
212
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(233 citation statements)
references
References 23 publications
20
212
1
Order By: Relevance
“…For thin films, 3,4,5,6 nanowires, 7,8 and nanocrystals 9,10 the geometric constraints will have an impact on martensite formation. Recently, Frick et al 11 experimentally studied the stress-strain behavior of nanopillars of nickel titanium shape-memory alloys (SMA), using nanoindentation tests.…”
Section: Introductionmentioning
confidence: 99%
“…For thin films, 3,4,5,6 nanowires, 7,8 and nanocrystals 9,10 the geometric constraints will have an impact on martensite formation. Recently, Frick et al 11 experimentally studied the stress-strain behavior of nanopillars of nickel titanium shape-memory alloys (SMA), using nanoindentation tests.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unique mechanical, thermal, electrical and optical properties, materials with nanometer-sized structure have attracted a great deal of interest as potential building blocks in nanoelectronic and nanoelectromechanical devices [1]. Many researchers have demonstrated, through both experiments and analysis, that the structure and properties of nanowires can be quite different from those of bulk materials due to the effect of the large surface to volume ratio [2][3][4][5][6][7][8][9][10][11][12][13][14].Recently, Uchic et al [15,16] and Greer et al [17,18] reported that the plastic deformation behavior of single-crystalline sub-micropillars is dependent on the size of the pillar, even without a deformation gradient. More recently, a ''mechanical annealing" test was used to demonstrate that dislocations can be swept out of the samples through the progressive activation and exhaustion of dislocation sources [19].…”
mentioning
confidence: 99%
“…More recently, a ''mechanical annealing" test was used to demonstrate that dislocations can be swept out of the samples through the progressive activation and exhaustion of dislocation sources [19]. These promising results raise an important question: is the size effect still operative when the size of the pillar is reduced to under 10 nanometers?Despite many efforts [6][7][8][9][10][11][12][13][14], a quantitative understanding of dislocation flow in nanoscale metals has remained elusive. In particular, the correlation of the dislocation flow with the stress-strain curve is of great interest, for the underlying mechanisms are typically represented by a mechanical response in macroscopic level experiments.…”
mentioning
confidence: 99%
See 2 more Smart Citations